Citalopram-mediated anxiolysis and differing neurobiological responses in both sexes of a genetic model of depression - Kokras, N; Sotiropoulos, I; Pitychoutis, P M; Almeida, O. F.; Papadopoulou-Daifoti, Z. (Neuroscience, 2011)
Disorders such as depression and anxiety exhibit strong sex differences in their prevalence and incidence, with women also differing from men in their response to antidepressants. Furthermore, receptors for corticotrophin releasing hormone (CRHR1) and arginine vasopressin receptor subtype 1b (AVPR1b) are known to contribute to the regulation of mood and anxiety. In the present study, we compared the anxiety profile and CRHR1 and AVPR1b expression levels in control Sprague-Dawley (SD) rats and rats of the SD-derived Flinders Sensitive Line (FSL), a genetic model of depression. Additionally, given the apparent sex differences in the therapeutic efficacy of antidepressants and because antidepressants are commonly used to treat comorbid anxiety and depressive symptoms, we assessed whether the anxiolytic effects of an antidepressant occur in a sex-dependent manner. Male and female FSL rats were treated with citalopram 10 mg/kg once daily for 14 days and were then tested in the open field and the elevated plus maze paradigms. Upon completion of the behavioural analysis, AVPR1b and CRHR1 expression levels were monitored in the hypothalamus and the prefrontal cortex (PFC) using Western blotting. According to our results, male FSL rats were more anxious than control SD rats, a difference abolished by citalopram treatment. Baseline anxiety levels were similar in female FSL and SD rats, and citalopram further reduced anxiety in female FSL rats. Importantly, whereas citalopram altered AVPR1b expression in the hypothalamus of male FSL rats, its actions on this parameter were restricted to the PFC in female FSL rats. In both sexes of FSL rats, citalopram did not alter CRHR1 expression in either the hypothalamus or PFC. Our results demonstrate that antidepressant treatment reduces anxiety levels in FSL rats of both sexes: the magnitude of treatment effect was related to the starting baseline level of anxiety and the antidepressant elicited sexually differentiated neurobiological responses in specific brain regions.
Keywords: *Sex Characteristics; Animals; Anti-Anxiety Agents/pharmacology; Antidepressive Agents, Second-Generation/pharmacology; Citalopram/*pharmacology; Depressive Disorder/*drug therapy/*genetics/physiopathology; Disease Models, Animal; Female; Male; Rats; Rats, Sprague-Dawley; Receptors, Corticotropin-Releasing Hormone/genetics/metabolism; Receptors, Vasopressin/genetics/metabolism; Selective Serotonin Reuptake Inhibitors/pharmacology